Self-presentation of the Veterinarian: Does it Affect Clients’ Perception in Bosnia and Herzegovina? - Lutvikadic, Ismar; Spahija, Nermina; Å unje-Rizvan, Amila; FilipoviÄ‡, Selma; ObhoÄ‘aÅ¡, Muamer; MaksimoviÄ‡, Alan (Journal of Advanced Veterinary Research, 2023)
Parallel with professional skills, verbal and non-verbal communication should be mastered by veterinarians in order to improve the quality of the â€œveterinarian-owner-patientâ€ relationship. Non-verbal communication implies facial expressions and attitude, but professionalâ€™s attire can be an influencing factor as well. The effect that veterinarian self-presentation has on clientsâ€™ perceptions of veterinarians was not investigated previously in Bosnia and Herzegovina (B&H). Therefore, the aim of this study was to examine the perception of animal owners from B&H regarding veterinariansâ€™ verbal and nonverbal communication skills, presentation on social media and professional attire. The questionnaire was compiled in Google form and consisted of an introduction and 13 questions followed by an explanation. A total of 648 clients participated in the survey between February and April 2023. Obtained data were processed in Microsoft Excel using descriptive statistics. Results of our survey indicate that veterinariansâ€™ attire, along with verbal communication, plays a significant role in gaining trust and comfort from animal owners in B&H. Given that it is currently not present, we recommend inclusion of verbal and non-verbal communication skills as a mandatory subject or module in the undergraduate study curriculum of veterinary medicine in B&H.